Tibial nerve stimulation compared with sham to reduce incontinence in care home residents: ELECTRIC RCT. - Booth, Joanne (Health Technol Assess, 2021)
BACKGROUND: Urinary incontinence is prevalent in nursing and residential care homes, and has a profound impact on residents' dignity and quality of life. Treatment options are limited in these care contexts and care homes predominantly use absorbent pads to contain incontinence, rather than actively treat it. Transcutaneous posterior tibial nerve stimulation is a non-invasive, safe, low-cost intervention that is effective in reducing urinary incontinence in adults. OBJECTIVE: To determine the clinical effectiveness of transcutaneous posterior tibial nerve stimulation to treat urinary incontinence in care home residents and to determine the associated costs of the treatment. DESIGN: A multicentre, pragmatic, participant and outcome assessor-blind, randomised placebo-controlled trial. SETTING: A total of 37 UK residential and nursing care homes. PARTICIPANTS: Care home residents with at least weekly urinary incontinence that is contained using absorbent pads and who are able to use a toilet/toilet aid with or without assistance. INTERVENTIONS: Residents were randomised (1 : 1) to receive 12 30-minute sessions of transcutaneous posterior tibial nerve stimulation or sham stimulation over a 6-week period. MAIN OUTCOME MEASURES: Primary outcome - change in volume of urine leaked over a 24-hour period at 6 weeks. Secondary outcomes - number of pads used, Perception of Bladder Condition, toileting skills, quality of life and resource use. RESULTS: A total of 408 residents were randomised (transcutaneous posterior tibial nerve stimulation, n = 197; sham stimulation, n = 209); two exclusions occurred post randomisation. Primary outcome data were available for 345 (85%) residents (transcutaneous posterior tibial nerve stimulation, n = 167; sham stimulation, n = 178). Adherence to the intervention protocol was as follows: 78% of the transcutaneous posterior tibial nerve stimulation group and 71% of the sham group received the correct stimulation. Primary intention-to-treat adjusted analysis indicated a mean change of -5 ml (standard deviation 362 ml) urine leakage from baseline in the transcutaneous posterior tibial nerve stimulation group and -66 ml (standard deviation 394 ml) urine leakage in the sham group, which was a statistically significant, but not clinically important, between-group difference of 68-ml urine leakage (95% confidence interval 0 to 136 ml; p = 0.05) in favour of the sham group. Sensitivity analysis supported the primary analysis. No meaningful differences were detected in any of the secondary outcomes. No serious adverse events related to transcutaneous posterior tibial nerve stimulation were reported. Economic evaluation assessed the resources used. The training and support costs for the staff to deliver the intervention were estimated at £121.03 per staff member. Estimated costs for delivery of transcutaneous posterior tibial nerve stimulation during the trial were £81.20 per participant. No significant difference was found between participants' scores over time, or between transcutaneous posterior tibial nerve stimulation and sham groups at any time point, for resident or proxy quality-of-life measures. CONCLUSIONS: The ELECTRIC (ELECtric Tibial nerve stimulation to Reduce Incontinence in Care homes) trial showed, in the care home context (with a high proportion of residents with poor cognitive capacity and limited independent mobility), that transcutaneous posterior tibial nerve stimulation was not effective in reducing urinary incontinence. No economic case for transcutaneous posterior tibial nerve stimulation was made by the cost-consequences analysis; however, the positive reception of learning about urinary incontinence for care home staff supports a case for routine education in this care context. LIMITATIONS: Completing 24-hour pad collections was challenging for care home staff, resulting in some missing primary outcome data. FUTURE WORK: Research should investigate transcutaneous posterior tibial nerve stimulation in residents with urgency urinary incontinence to determine whether or not targeted stimulation is effective. Research should evaluate the effects of continence training for staff on continence care in care homes. TRIAL REGISTRATION: Current Controlled Trials ISRCTN98415244 and ClinicalTrials.gov NCT03248362. FUNDING: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 25, No. 41. See the NIHR Journals Library website for further project information.